Clinical governance in Australia. Issue 2 (7th April 2015) - Spigelman, Allan D; Rendalls, Shane
Abstract : Purpose: – The purpose of this paper is to overview, background and context to clinical governance in Australia, areas for further development and potential learnings for other jurisdictions. Design/methodology/approach: – Commentary; non-systematic review of clinical governance literature; review of web sites for national, state and territory health departments, quality and safety organisations, and clinical colleges in Australia. Findings: – Clinical governance in Australia shows variation across jurisdictions, reflective of a fragmented health system with responsibility for funding, policy and service provision being divided between levels of government and across service streams. The mechanisms in place to protect and engage with consumers thus varies according to where one lives. Information on quality and safety outcomes also varies; is difficult to find and often does not drill down to a service level useful for informing consumer treatment decisions. Organisational stability was identified as a key success factor in realising and maintaining the cultural shift to deliver ongoing quality. Research limitations/implications: – Comparison of quality indicators with clinical governance systems and processes at a hospital level will provide a more detailed understanding of components most influencing quality outcomes. Practical implications: – The information reported will assist health service providers to improve information and processes to engage with consumers and build further transparency and accountability. Originality/value: – In this paper the authors have included an in depth profile of the background and context for the current state of clinical governance in Australia. The authors expect the detail provided will be of use to the international reader unfamiliar with the nuances of the Australian Healthcare System. Other studies (e.g. Russell and Dawda, 2013; Phillips et al., n.d.) have been based on deep professional understanding of clinical governance in appraising and reporting on initaitives and structures. This review has utilised resources available to an informed consumer seeking to understand the quality and safety of health services.